GREEN GROWTH EDUCATION FOR SUSTAINABLE DEVELOPMENT - I Made Putrawan (Jurnal Green Growth dan Manajemen Lingkungan, 2012)
AbstractOne of the important factors that has been difficult to be overcome by each country is poverty, beside unemployment and environmental degradation. To eradicate the poverty is one of the goals of each government in this planet to build a social justice. For instance, among Asian-Pacific countries, the economic growth has indicated a tremendous progress, but at the same time most people still live beyond the poverty line and the quality of our environment is still unsolvable. Therefore, the postulate â€œgrowth first, clean up laterâ€ is no longer applicable. The concept of â€œgreen growthâ€ which was declared in Soul (2008) by Asian-Pacific countries might be more suitable in integrating sustainable development for social justice, since one of the approaches to be implemented in green growth is how to involve the poor people in developing the economic sector. Involving the poor people is one of the forms of social justice. So, how students understand those concepts and are there any difference in understanding those concepts among level of study, by conducting a comparative research, is the main topic of this paper. An ex post facto method used and involving students who are now at the undergraduate, master and doctorate programs, at the State University of Jakarta. Around 25 undergraduate students (for batch 2 is 39 & 21), 22 master batch 2 is 20 students), and 22 doctorate (24 for batch 2) students have been selected randomly. The instrument for measuring students understanding green growth has been developed based on (1)Sustainable Consumption and Production (Demand-side), (2) green business, (3) sustainable infrastructure, (4) green tax and Budget Reform, (5) Investment in Natural Capital, and (6) Eco-efficiency Indicators. By applying one-way ANOVA, this research reveals that there is significant and very highly significant (batch 2) difference exist among groups being compared, means that green growth education has an impact on studentsâ€™ understanding about green growth for social justice, especially in sustainable development. Finally, it will be easier for them to socialize and improve the implementation of sustainable development. Therefore, intentionally, it is a basic way for eradicating the poverty by accomplishing social justice in sustainable development through education.